Focusing Hemispherical Waves - Colin J. R. Sheppard (Photonics)
The field in the focal plane of a hemispherically focused wave in an aplanatic optical system can be expressed in an analytical form. In fact, many different cases of hemispherically focused scalar and vectorial waves can be analytically expressed. We consider focusing with linear or circular polarized illumination as well as other cases such as electric dipole, transverse electric, and radial polarizations. We also investigate 4Pi focusing and the focusing of vortex waves. These results can be applied to focusing with microscope objectives of high numerical aperture.